(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This in the article combinational drying technologies theoretical basics, practical their use and efficiency analysis done. Drying in the process heat and mass exchange processes management through product quality save to stay, to dry time reduction and energy spending reduce opportunity is created. Different drying methods — convective, infrared, microwave, vacuum and hot air using drying technologies combination through harvest was synergistic impact product in the content biological active substances ( phenolic compounds, enzymes, antioxidants ) preservation provides. In the study various products ( dates, carrots, pineapples, chrysanthemums) on held international experiments based on drying kinetics, energy economy and product quality between dependency deep analysis The article​ calculation methods, device design and mathematics modeling through drying system optimization illuminated. Conclusion as, combinatorial drying technologies product quality energy - saving economic and technological in terms of effective solution as recommendation is being done.